Respuesta :

Answer:

2 Al(s) + 3 H₂SO₄(aq) ⇒ Al₂(SO₄)₃(aq) + 3 H₂(g)

Explanation:

Let's consider the unbalanced equation for the single replacement reaction between Al and H₂SO₄.

Al(s) + H₂SO₄(aq) ⇒ Al₂(SO₄)₃(aq) + H₂(g)

We will begin balancing S atoms by multiplying H₂SO₄ by 3.

Al(s) + 3 H₂SO₄(aq) ⇒ Al₂(SO₄)₃(aq) + H₂(g)

Then, we balance Al atoms by multiplying Al by 2.

2 Al(s) + 3 H₂SO₄(aq) ⇒ Al₂(SO₄)₃(aq) + H₂(g)

Finally, we get the balanced equation by multiplying H₂ by 3.

2 Al(s) + 3 H₂SO₄(aq) ⇒ Al₂(SO₄)₃(aq) + 3 H₂(g)

ACCESS MORE